Nigella sativa as a galactagogue: a systematic review - Aini Farzana Zulkefli,; Ruszymah Hj Idrus,; Adila A. Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Nigella sativa is a herb with various pharmacological properties and has been used widely for medicinal purposes and acts as a milk booster. The aim of this systematic review was to provide information on the galactagogue property of N. sativa. Electronic searches were conducted in two databases, namely, Medline via EBSCOhost and Scopus, for relevant studies published between the 1865 and March 2020. Additional records identified through Google Scholar showed one eligible article. Only articles published in English and related to the galactagogue effect of N. sativa were included in this review. A total of 110 potential articles were identified, but only four fulfilled the inclusion criteria. Four animal studies were included in this review. All of the selected studies reported positive galactagogue effects of N. sativa as determined by serum prolactin level, breast tissue changes, milk production and composition, and weight of litter, thereby suggesting its effect as milk booster. However, the review found no evidence supporting the effect of N. sativa as a galactagogue in humans.